Estudo químico e histoquímico das glândulas metapleural e labial de formigas cortadeiras e a influência destas nas relações simbiontes presentes nos jardins de fungo - Malaquias, Karla da Silva (2015)
Leaf-cutting ants are considered the most derived insects on the planet. The performance in maintaining the aseptic conditions of the colonies is a key factor of the ecological success of these ants. Several defenses are used by ants, among them stand out chemical defense and mutualistic associations. The last of which is variable as it is dependende the species and / or environment in which they are the nests. So this article aims at a more detailed study the action of chemical defense mode, the form it manifests itself in different species of leaf-cutting ants, which have different degrees of derivation. The study was divided into two parts, the first investigated the chemical and histochemical composition of metapleural and labial glands of five species of leaf-cutting ants. Acids and hydroxy acids were identified and quantified, as main cosntituintes. These have antimicrobial action to pathogens present in the colony. The concentration and ratio of the compounds is directly related to species and variety. Histochemical analyzes revealed great similarity between species, demonstrating a relationship with the function of these glands. Enzymes that play an important role in the social order were evidenced by histoenzimáticos experiments. In the second part, as it was known the morphology of the glands, the search for inhibitors of enzymes present in the gland that provide natural protection to the colony to break the natural chemical defense. An enzyme that plays a major role in the secretion of acid is the fatty-acid synthase (FAS). At the present stage, cerulenin analogues were synthesized, known inhibitors of FAS in order to study the structure-activity relationship of these compounds.